2,2,6-Trimethyl-5-[2-(4-methylphenyl)ethynyl]-4H-1,3-dioxin-4-one - Caracelli, Ignez [UNESP]; Zukerman-Schpector, Julio; Vieira, Adriano S.; Stefani, Helio A.; Tiekink, Edward R. T. (Wiley-Blackwell, 2009)
The 1,3-dioxin-4-one ring in the title compound, C(16)H(16)O(3), is in a half-boat conformation with the quaternary O-C(CH(3))(2)-O atom lying 0.546 (1) angstrom out of the plane defined by the remaining five atoms. The crystal structure is consolidated by C-H center dot center dot center dot O contacts that lead to supramolecular layers.